Petrochronology of anatectic rocks from Nazaré Paulista (SP), southern Socorro Guaxupé Nappe - Virmond, Adrianna Luiza (2019)
In the southern portion of Socorro Guaxupé Nappe, interpreted as a magmatic arc developed during west Gondwana assembly in the Brasiliano-Pan-African Orogeny, Nazaré Paulista region is characterized by the occurrence of complex outcrops of migmatites and anatectic granites. The anatectic granites present two main types: a veined garnet-biotite granite (gray granite); and garnet leucogranites, that occur both as independent bodies, and as veins, forming complex networks cutting the gray granite. Field evidence points to an apparent crystallization gap between granite varieties, which we investigate in this dissertation, applying zircon and monazite geochronology (by SHRIMP and LA-ICP-MS, respectively). We also investigate the genesis of the leucogranites, using trace-element signatures of zircon and garnet. Obtained SHRIMP zircon ages for host gray granite and leucogranite veins are equivalent, within error - 626 ± 8 and 618 ± 8 Ma, respectively. These ages record near peak and part of the retrograde evolution of the region. Monazite LA-ICP-MS dating confirms the crystallization age gap between the granite varieties: the monazite from gray granite crystallized at ca. 621 ± 2 Ma, while monazite from leucogranites crystallized, probably in episodic pulses, between 610 - 600 Ma. Zircon inheritance sets in the migmatite vary from 1100 to 2450 Ma. Some inherited monazite cores from migmatite also yielded ages of ca. 770 - 790 Ma, coeval to very low Th/U zircon rims. Combined monazite and zircon geochronological data suggests a protracted thermal last event, recording part of the prograde and mostly the retrograde path of the region, during a time span longer than 30 Ma. Detrital zircon from the metatexite suggest a maximum deposition age of at least 1100 Ma, and a chemical signature of granitoid sources. The inherited zircon and monazite suggest a metamorphic event at ca. 790 Ma, rarely reported to Socorro Guaxupé Nappe, but coeval to the metamorphism registered by rocks in the Apiaí-Embu Terrane (Mantiqueira Orogenic System). Modelling bulk rock contents from zircon compositions, in late zircon phases, occurring as overgrowths, produce bulk rock compositions compatible empirical data, suggesting these phases were in equilibrium and no hydrothermal event modified these grains. Ti in zircon thermometry and zircon/garnet modelling suggest evolution in an open system for these rocks. We calculated \'D POT. zircon/garnet IND. REE\' and applied the method proposed by Taylor et al. (2017). Zircon cores are close equilibrium with (what is interpreted as) restitic garnet and overgrowths are usually in equilibrium with late, peritectic garnet generation. However, for some varieties of leucogranite, zircon and garnet are never found to be in equilibrium. No coherence between Lu-Hf isotopy is found between the vein leucogranite and the gray granite, so, if the gray granite is a source for the veins, another source is necessary to account for isotopic variation. The garnet leucogranite present trends compatible with fractioned crystallization, while the fibrolite bearing leucogranite probably formed in an open system. Nazaré Paulista evolution is much more complex than previously thought: a primary anatexis event, after metamorphic peak, at around 630 - 625 Ma originated the gray granite; a second anatexis event, probably involving water-flux melting of the gray granite, during decompression, generated the leucogranites, which crystallized at 610 - 600 Ma.